Implementation of the Exponential Comparison Method (ECM) in Selecting E-Commerce Satisfaction in Gang Ranim - Karan Alifian Mulya; Feri Alpiyasin (Politeknik Mardira Indonesia, 2026)
The development of e-commerce provides many platform options for people to conduct online buying and selling transactions. The large number of e-commerce alternatives often makes it difficult for users to determine the most satisfactory platform. This study aims to implement the Exponential Comparison Method (MPE) as a decision support system to determine the level of satisfaction with e-commerce in the Gang Ranim area. The criteria used include user friendliness, ease of transaction, product quality, delivery speed, and seller service. The MPE method was chosen because it is able to provide a more explicit weighting of the level of importance of criteria through an exponential function. The results of the study indicate that the MPE method can help users in determining e-commerce with the best level of satisfaction objectively and systematically. Keywords: Decision Support System, Exponential Comparison Method, Customer Satisfaction, E- Commerce;